Strategi Pengembangan Game Digital Berbasis Keterampilan Executive Function Anak Usia Dini - Roby Naufal Arzaqi; Deri Hendriawan; Aisah Karunia Rahayu (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2024)
The purpose of this study is to create an approach to digital games that can improve early childhood executive functioning, which consists of three main components: working memory, inhibitory control, and cognitive flexibility. In addition, they also wanted to find out how effective digital games designed specifically to train early childhood executive skills were. The research method is D&D (Design and Development), which is based on the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model from Robert Maribe Branch. The focus of the research is the design stage of development. Therefore, the implementation and evaluation stages will be carried out in the next study. Data were collected through questionnaires, and quantitative descriptive analysis was used to analyze the data. The results of the study focus on strategies in facilitating executive function skills in the form of working memory, thinking flexibility and self-control which involve remembering, categorizing and levels and obstacles. Thus, this article is expected to provide valuable insights for researchers, game developers, and aspiring educators and practitioners in the development of executive skills through digital games.